Electrochemical behaviour of denatured haemoglobin at the liquid|liquid interface - Herzog, G.; Eichelmann-Daly, P.; Arrigan, Damien (Elsevier, 2010)
We report here the influence of chemical denaturation of haemoglobin on its electrochemical behaviour at the polarised liquid|liquid interface. Denaturation with urea resulted in a modification of the haemoglobin electrochemical behaviour, with the disappearance of the forward transfer peak and a decrease of the reverse peak current. Although the reverse peak current increased linearly with the concentration of denatured haemoglobin in the aqueous phase, the slope of the current-concentration plot was three times lower than that for native haemoglobin over the 0.1-1 μM concentration range. These results indicate the sensitivity of electrochemistry at liquid|liquid interfaces to protein tertiary structure.